2022
DOI: 10.3390/nu14163433
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Non-Invasive Stratification of Coronary Artery Disease and Prognostic Impact on Long-Term Survival in Patients with Stable Coronary Heart Disease

Abstract: Knowledge about cardiac and inflammatory biomarkers in patients with stable coronary artery disease (CAD) is limited. To address this, we analyzed 3072 patients (36% female) with a median follow-up of 10 years in the Leipzig LIFE Heart Study with suspected CAD with coronary angiography. Selected biomarkers included troponin T (hsTNT), N-terminal pro B-type natriuretic peptide (NT-proBNP), copeptin, C-reactive protein (hsCRP), and interleukin-6 (IL-6). Patients were stratified by CAD severity: CAD0 (no sclerosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Biomarkers improve prediction of long-term mortality in CAD patients when compared to established risk prediction algorithms and might allow more accurate classification of patients with stable CAD, enabling physicians to choose more personalized treatment regimens for their patients [43,44]. Incorporation of cardiac troponins, NT-proBNP, copeptin, and IL-6 improved risk prediction in CAD patients even after adjustment for classical risk factors [45]. Biomarkers of endothelial dysfunction and inflammation are promising targets for preventive or therapeutic strategies aimed at protecting the endothelium or reversing endothelial damage in CAD and related complications [46].…”
Section: Contemporary and Future Roles Of Biomarkers In Cadmentioning
confidence: 99%
“…Biomarkers improve prediction of long-term mortality in CAD patients when compared to established risk prediction algorithms and might allow more accurate classification of patients with stable CAD, enabling physicians to choose more personalized treatment regimens for their patients [43,44]. Incorporation of cardiac troponins, NT-proBNP, copeptin, and IL-6 improved risk prediction in CAD patients even after adjustment for classical risk factors [45]. Biomarkers of endothelial dysfunction and inflammation are promising targets for preventive or therapeutic strategies aimed at protecting the endothelium or reversing endothelial damage in CAD and related complications [46].…”
Section: Contemporary and Future Roles Of Biomarkers In Cadmentioning
confidence: 99%
“…There have been numerous attempts to identify reliable markers of coronary artery disease using molecular techniques. Troponin-T, troponin-I, and high-sensitivity troponin-T [10] are the most accurate markers in cardiovascular patients. Postmortem research has shown that troponin-T is not a specific marker for acute myocardial injury [11].…”
mentioning
confidence: 99%